Grace For President - DiPucchio, Kelly; Pham, LeUyen; Rose, Anika Noni, 1972-; Hyperion (Publisher); Disney Book Group (New York : Disney/Hyperion Books, 2012)
When Grace discovers that there has never been a female U.S. president, she decides to run for school president.
"Published by Disney/Hyperion Books, an imprint of Disney Book Group."--Opposite title page.
Keywords: Presidents -- United States; Election; Juvenile fiction; Political campaigns -- United States; Fiction; Elections; Juvenile fiction; Sexism; Juvenile fiction; Schools; Juvenile fiction; Elections -- Fiction; Presidents -- Fiction; Sexism -- Fiction; Schools -- Fiction; Elections -- Fiction; Presidents -- Fiction; Sexism -- Fiction; Schools; Fiction